EXPERIMENTAL TESTING OF COMPOSITE SANDWICH PANELS WITH DIFFERENT FACE SHEETS - Trombeva-Gavriloska, Ana; Lazarevska, Marijana; Cvetkovska, Meri (Journal of Applied Engineering Science, 2016)
An experimental tests performed on two series of sandwich panels, differed by the type of the matrix used for the composite face sheets, are presented in this paper. By applying a linear load in the middle of the span, these sandwich panels were subjected on three points bending test. The analysis was performed in order to evaluate the influence of the matrix type on the ultimate mechanical characteristics of the sandwich panels. By analyzing the F-δ behavior of the sandwich panels, as well as the F-σ behavior of the composite face sheets, the influence of the matrix type used in the composite face sheets has been evaluated.